Motif orientation matters: Structural characterization of TEAD1 recognition of genomic DNA - Filandrová, Růžena; Vališ, Karel; Černý, Jiří; Chmelík, Josef; Slavata, Lukáš; Fiala, Jan; Rosůlek, Michal; Kavan, Daniel; Man, Petr; Chum, Tomáš; Cebecauer, Marek; Fabris, Daniele; et al. (Structure (London, England, 2021)
TEAD transcription factors regulate gene expression through interactions with DNA and other proteins. They are crucial for the development of eukaryotic organisms and to control the expression of genes involved mostly in cell proliferation and differentiation; however, their deregulation can lead to tumorigenesis. To study the interactions of TEAD1 with M-CAT motifs and their inverted versions, the KD of each complex was determined, and H/D exchange, quantitative chemical cross-linking, molecular docking, and smFRET were utilized for structural characterization. ChIP-qPCR was employed to correlate the results with a cell line model. The results obtained showed that although the inverted motif has 10× higher KD, the same residues were affected by the presence of M-CAT in both orientations. Molecular docking and smFRET revealed that TEAD1 binds the inverted motif rotated 180°. In addition, the inverted motif was proven to be occupied by TEAD1 in Jurkat cells, suggesting that the low-affinity binding sites present in the human genome may possess biological relevance.
Keywords: Jurkat Cells; Protein Binding; nukleotidové motivy; Jurkat buňky; TEA Domain Transcription Factors; jaderné proteiny; DNA vazebné proteiny; Molecular Docking Simulation; simulace molekulového dockingu; vazba proteinů; structural mass spectrometry; native electrospray; lidé; Transcription Factors; transkripční faktory; Humans; hydrogen-deuterium exchange; chemical cross-linking and single molecule FRET; high- and low-affinity binding sites; transkripční faktory TEA domény; DNA; M-CAT; Nucleotide Motifs; TEAD1; Nuclear Proteins; DNA-Binding Proteins; transcription factor; DNA binding